A non-invasive measurement of tongue surface temperature. (February 2019) - Lv, Cong; Wang, Xinmiao; Chen, Jianshe; Yang, Ni; Fisk, Ian
Abstract: Oral temperature, tongue specifically, is a key factor affecting oral sensation and perception of food flavour and texture. It is therefore very important to know how the tongue temperature is affected by food consumption. Unfortunately, traditional methods such as clinical thermometers and thermocouples for oral temperature measurement are not most applicable during food oral consumption due to its invasive nature and interference with food. In this study, infrared thermal (IRT) imager was investigated for its feasibility for the measurement of tongue surface temperature. The IRT technique was firstly calibrated using a digital thermometer (DT). The technique was then used to measure tongue surface temperature after tongue was stimulated by (1) water rinsing at different temperatures (0–45 °C); and (2) treated with capsaicin solutions (5, 10, and 20 ppm). For both cases, tongue surface temperature showed significant changes as a result of the physical and chemical stimulation. Results confirm that IRT is feasible for tongue temperature measurement and could be a useful supporting tool in future for the study of food oral processing and sensory perception. Graphical abstract: Unlabelled Image Highlights: IRT is a fast, non-contact and non-invasive technique for tongue temperature measurement. Tongue surface temperature varied significantly after water rinsing at different temperatures. Tongue surface remained at a higher temperature after capsaicin treatment. IRT is a useful tool for tongue temperature measurement during food oral processing.